Regulator and enzyme specificities of the TOL plasmid-encoded upper pathway for degradation of aromatic hydrocarbons and expansion of the substrate range of the pathway. - Abril, M A (1989)
The TOL plasmid upper pathway operon encodes enzymes involved in the catabolism of aromatic hydrocarbons such as toluene and xylenes. The regulator of the gene pathway, the XylR protein, exhibits a very broad effector specificity, being able to recognize as effectors not only pathway substrates but also a wide variety of mono- and disubstituted methyl-, ethyl-, and chlorotoluenes, benzyl alcohols, and p-chlorobenzaldehyde. Benzyl alcohol dehydrogenase and benzaldehyde dehydrogenase, two upper pathway enzymes, exhibit very broad substrate specificities and transform unsubstituted substrates and m- and p-methyl-, m- and p-ethyl-, and m- and p-chloro-substituted benzyl alcohols and benzaldehydes, respectively, at a high rate. In contrast, toluene oxidase only oxidizes toluene, m- and p-xylene, m-ethyltoluene, and 1,2,4-trimethylbenzene [corrected], also at a high rate. A biological test showed that toluene oxidase attacks m- and p-chlorotoluene, albeit at a low rate. No evidence for the transformation of p-ethyltoluene by toluene oxidase has been found. Hence, toluene oxidase acts as the bottleneck step for the catabolism of p-ethyl- and m- and p-chlorotoluene through the TOL upper pathway. A mutant toluene oxidase able to transform p-ethyltoluene was isolated, and a mutant strain capable of fully degrading p-ethyltoluene was constructed with a modified TOL plasmid meta-cleavage pathway able to mineralize p-ethylbenzoate. By transfer of a TOL plasmid into Pseudomonas sp. strain B13, a clone able to slowly degrade m-chlorotoluene was also obtained.